Juan Cruz Alli Aranguren - Jimeno Aranguren , Roldán (Huarte de San Juan. Geografía e Historia, 2014)
Juan Cruz Alli Aranguren has devoted much of his research on the History of Law. Among his areas of research include those relating to the construction of the Spanish Administrative Law, the paradigms of legality in the French Administrative Law, the autonomous regime and the environment. Regarding the regime of Navarra has studied the economic agreements with Spain, local, provincial and foral institutional system, the forestry regime, and environmental heritage. Professor of Administrative Law until his retirement in 2013. He also has an extensive political and institutional history, which has led him to be a member of the Parliament of Navarre (1983-2011), President of the Government of Navarre (1991-1995) and Vice President and Minister of Finance (1995-1996).
Keywords: Juan Cruz Alli; History of Law; Administrative Law; Government of Navarre; Parliament of Navarre